2004
DOI: 10.1023/b:cemn.0000012722.45805.c8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Signals into the Insular Cortex and Amygdala During Aversive Gustatory Memory Formation

Abstract: In this paper, we will provide evidence of the putative molecular signals and biochemical events that mediate the formation of long-lasting gustatory memory trace. When an animal drinks a novel taste (the conditioned stimulus; CS) and it is later associated with malaise (unconditioned stimulus; US), the animal will reject it in the next presentation, developing a long-lasting taste aversion, i.e., the taste cue becomes an aversive signal, and this is referred to as conditioning taste aversion. Different eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 61 publications
4
33
0
1
Order By: Relevance
“…Lamprecht et al (35) also showed that inhibition of cAMP response element-binding protein (CREB), one of the regulatory transcriptional factors for c-fos gene expression, in the AMY with in vivo AS-ODN technology disrupted the retention, but not the acquisition, of CTA. In line with these results, Bermudez-Rattoni and colleagues (36,37) have suggested that positive interaction between the basolateral AMY-IC enhances the strength of long-term CTA memory.…”
Section: Discussionmentioning
confidence: 62%
“…Lamprecht et al (35) also showed that inhibition of cAMP response element-binding protein (CREB), one of the regulatory transcriptional factors for c-fos gene expression, in the AMY with in vivo AS-ODN technology disrupted the retention, but not the acquisition, of CTA. In line with these results, Bermudez-Rattoni and colleagues (36,37) have suggested that positive interaction between the basolateral AMY-IC enhances the strength of long-term CTA memory.…”
Section: Discussionmentioning
confidence: 62%
“…Humans and other animals can be conditioned to avoid food. Such conditioned taste aversion leads to many documented changes in the brain, in particular, changes in cholinergic and glutamatergic activity (23). It is unclear whether false food beliefs and their accompanying food avoidance, like those observed here, produce neural reorganization similar to that evident with true memories of bad food experiences (24,25).…”
Section: Discussionmentioning
confidence: 65%
“…Thus the use of CTA, allows the investigation of the processes involved in both the acquisition and extinction of aversive memories. 30,35 We have established that BALB/c mice are a useful strain for assessing CTA, 36 so we used this strain for our initial pharmacological studies. Also, the time course of extinction in this mouse strain is relatively long (approximately 4-5 days) and, therefore, amenable to assess potential facilitatory responses.…”
Section: Cta Following Amn082mentioning
confidence: 99%